The memory clinic and psychosocial intervention: Translating past promise into current practices - Esme Moniz-Cook; Gail Mountain (Frontiers in Rehabilitation Sciences, 2023)
Disproportionate negative effects since the pandemic have amplified the already limited post-diagnostic support for older people with dementia. This paper summarizes an exploratory randomized controlled study of a proactive family-based intervention compared with “usual” post-diagnostic dementia care. Memory clinic practitioners collaborated with the family doctor (GP) to coordinate this. At 12-month follow-up, positive effects on mood, behavior, carer coping and maintenance of care at home were found. Current approaches to deliver post-diagnostic support in primary care may require rethinking since (i) GP workloads have increased with low numbers of GPs per head of population in parts of England; and (ii) unlike many other long-term conditions, ongoing stigma, fear and uncertainty associated with dementia adds to the huge complexity of timely care provision. There is a case for return to a “one-stop facility”, with a single pathway of continuing multidisciplinary coordinated care for older people with dementia and families. Future longitudinal research could compare structured post-diagnostic psychosocial intervention coordinated by skilled practitioners in a single locality memory service “hub”, against other approaches such support organized mostly within primary care. Dementia-specific instruments for outcome measurement are available for use in routine practice, and should be included in such comparative studies.